The social construction of normalcy in post-Yolanda Tacloban City the role played by business establishments - de la Cruz, Judee Anne C.; Luquing, Amanda Claire G.; Ogario, Mer Inisa D. (2015)
Normalcy in the context of this study refers to the restoration of normal community activities that were disrupted by disaster impacts. Consequently, the researchers sought to uncover how the reappearance of business establishments shaped the social construction of normalcy in post-Yolanda, Tacloban City.